Pengaruh Umpan Balik (Feedback) Guru Terhadap Keterampilan Menulis Anak pada Pembelajaran Bahasa Indonesia Kelas V SDN 2 Dragan - Wahyu Dewi Pratiwi (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
Feedback is the simple things but its having big influence to the students written skills. This research is aimed at feedback influence towards teacher’s written feedback 5th grade students. Three research questions were formulated in this study. (1) What types of written feedback does the teacher give on the students’ writing? (2) What categories of written feedback does the teacher give on the students’ writing? and (3) What are the teacher’s influences feedback towards student’s written skills in Indonesian subject in grade 5th?. The respondents of this study were 5th grade students of SD N 2 Dragan. This research belongs to descriptive qualitative. The main research instrument was the teacher’s influences feedback towards student’s written skills in Indonesian subject in grade 5th. The data were taken from the students‟ writing. The reseacher collected the students‟ writings that contain teacher‟s written feedback. The researcher used three instruments to gather data from the respondents: (1) Field note, (2) Questionnaire, and (3) Interview. The data analysis technique is the process of data arrangement and data categorization. In this study, the reseacher used triangulation to analyse the data.The result of descriptive analysis show that teacher‟s mostly gave feedback in direct way. Based on the third research question, it was discovered that (1) the students prefer written feedback than oral feedback (2) teacher‟s written feedback was objective, (3) teacher‟s written feedback was clear, (4) teacher‟s written feedback assisted the students (5) teacher‟s written feedback was encouraging, and (6) the students never had negative effect of the teacher‟s written feedback (7) teacher‟s written feedback did not disturb the process of writing (8) the teacher often gives feedback to the students.